Effect of Spacing and Nitrogen Fertilizer on Survival and Growth of Betula utilis - Aslam, Mehak; Sofi, P. A.; Masoodi, T. H.; Pala, Nazir A.; Rashid, Megna; Mugloo, J. A.; Dutt, Vaishnu (Indian Forester, 2021)
The present study reports the effect of spacing and nitrogen fertilizer on the growth and survival of Betula utilis seedlings under field conditions in temperate region of Kashmir Himalaya. The study was conducted at the field of Faculty of Forestry, Benhama, Ganderbal, SKUAST, Kashmir. The different levels of nitrogen fertilizer (25 kg N ha-1, 50 kg N ha-1 , 75 kg N ha-1 and 100 kg N ha-1) were applied to the Betula utilis seedlings that were transplanted in the field at two spacing viz., 60 Ã— 60 cm and 100 Ã— 100 cm to observe the effect of nitrogen fertilization and spacing on growth and survival of one year old seedlings in the field. The effect of spacing, fertilizer and their interaction (S x T) exert significant effect on survival and seedling growth parameters like height increment, collar diameter, number of leaves, leaf area, root biomass, shoot biomass and total plant biomass under open field conditions. Among these fertilizer doses, it was observed that application of 75 kg N ha-1 in two equal splits (first dose one month after transplanting and the second dose one month after the first application) to the seedlings of Betula utilis with 100 x 100 cm spacing was recorded to be the best treatment combination for producing more biomass per plant, healthy planting stock and for better plant survival. The present study exhibits that optimum levels of nitrogen and optimum